Kesiapsiagaan Keluarga Kelompok Rentan Ibu Hamil dalam Mengahadapi Bencana di Wilayah Kerja UPTD Puskesmas Talise - Elvaria Mantao; Nurhaya S. Patui (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Central Sulawesi is one of the provinces in Indonesia with the highest disaster incidence. This condition’s caused by the geography of Central Sulawesi which is located on a fault line with risk of disaster, and Palu City is the area with the highest risk of mental health of pregnant women must be prioritized in disaster management Pregnant women are considered a vulnerable group, as disasters can significantly affect both maternal well-being and fetal development. Family has an important role in reducing disaster risk. This study aims to analyze the preparedness of families with pregnant women in the Talise Health Center area, Palu City. Using an analytical survey with a quantitative, cross-sectional design, the research involved 77 pregnant women selected through stratified random sampling. Data was collected via questionnaires and analyzed using the Chi-Square Test. The findings revealed significant relationships between family preparedness and several factors: knowledge (p=0.000), emergency response plans (p=0.008), disaster warning systems (p=0.008), and resource mobilization (p=0.013). These results highlight the importance of increasing awareness and readiness at the family level. The results of this study strengthen the role of health workers and Posyandu cadres in providing preparedness information to pregnant women. Encourage the formation of pregnant women support groups in the community to share information and experiences related to disaster preparedness.